2021
DOI: 10.5194/essd-13-3513-2021
|View full text |Cite
|
Sign up to set email alerts
|

Long-term variations in actual evapotranspiration over the Tibetan Plateau

Abstract: Abstract. Actual terrestrial evapotranspiration (ETa) is a key parameter controlling land–atmosphere interaction processes and water cycle. However, spatial distribution and temporal changes in ETa over the Tibetan Plateau (TP) remain very uncertain. Here we estimate the multiyear (2001–2018) monthly ETa and its spatial distribution on the TP by a combination of meteorological data and satellite products. Validation against data from six eddy-covariance monitoring sites yielded root-mean-square errors ranging … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 46 publications
3
54
0
Order By: Relevance
“…A clear zonal seesaw pattern could be observed over the TP. The same analysis based on the remote sensing product derived from Han et al [28,29] also indicated that the first leading mode of summer SH showed significant consistent variations, and the second leading mode of summer SH showed a zonal dipolar pattern (Figure S1).…”
Section: Dominant Modes Of Variation In Summer Sh Over the Tpmentioning
confidence: 61%
See 2 more Smart Citations
“…A clear zonal seesaw pattern could be observed over the TP. The same analysis based on the remote sensing product derived from Han et al [28,29] also indicated that the first leading mode of summer SH showed significant consistent variations, and the second leading mode of summer SH showed a zonal dipolar pattern (Figure S1).…”
Section: Dominant Modes Of Variation In Summer Sh Over the Tpmentioning
confidence: 61%
“…This indicated that positive SH anomalies in the western TP are usually accompanied by negative SH anomalies in the eastern TP on an interannual time scale. Based on meteorological data and satellite products, a recent study found that the long-term variations of summer evapotranspiration (ET) over the TP present a dipole pattern, with an increasing trend in the eastern TP and a decreasing trend in the western TP [29]. It is worth studying the cause of opposite spatial patterns between SH and ET over the TP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite many available global reanalysis datasets, most of them have been found to be substantially biased on the QTP due to the presence of complex mountainous terrains and unique atmospheric circulation patterns (A. Wang & Zeng, 2012; L. Zhang et al., 2020; Zhou et al., 2021). The recently developed gridded reanalysis dataset, that is, the China Meteorological Forcing Dataset (CMFD) (He et al., 2020), is one of those widely used for the QTP studies (Han et al., 2021; T. Wang et al., 2019). It was created by fusing site‐scale observations from the China Meteorological Administration with existing reanalysis data, such as Global Land Data Assimilation System (GLDAS), Tropical Rainfall Measuring Mission, and Global Energy and Water Exchanges‐Surface Radiation (He et al., 2020; K. Yang et al., 2010).…”
Section: Datasets and Methodsmentioning
confidence: 99%
“…Note that the main differences between these products relate to the choice of meteorological and radiation forcing. Next, we estimated the multiyear (2001-2018) monthly terrestrial actual evapotranspiration (E) and its spatial distribution on the Tibetan Plateau (TP) using the surface energy balance system (SEBS) forced by a combination of meteorological data and satellite products [53].…”
Section: Evaluation and Generation Of Land Heat Fluxes And Evapotranspirationmentioning
confidence: 99%